IN VITRO HEPATOPROTECTIVE ACTIVITY OF APLOTAXIS AURICULATA IN HEPATOCYTES - NANDHINI R,; JEYADOSS T,; VELAVAN S, (International Journal of Pharma and Bio Sciences, 2014)
Liver plays a major role in detoxification. Any impairment to it or dysfunction may lead to many complication on one’s health. Treatment of liver diseases is still a challenge to modern medicine. The commerecially available medicine has little to offer for the alleviation of hepatic ailments but severe side effects. The study was aimed to evaluate in vitro hepatoprotective activity of Aplotaxis auriculata rhizome (200 and 400µg/ml) through CCl4 induced toxicity in hepatocytes. The phytochemical screening revealed the presence of flavonoids, terpenoids, triterpenoids, polyphenol and tannins. All the variables tested such as LPO, GSH, Protein, Bilirubin, ALP, SGOT and SGPT recorded a significant alteration observed in CCl4 exposed hepatocytes. However treatment with Aplotaxis auriculata extract restored the level and to near normal values was observed. The potential hepatoprotective activity of Aplotaxis auriculata is due to the presence of phytochemical constituents present in plant. Some of these phytochemicals such as flavonoids and polyphenolic compounds might have possessed hepatoprotective activity.